Peningkatan Keterampilan Berpikir Kreatif Melalui Model Project Based Learning Pada Peserta Didik Kelas IV Sekolah Dasar - Dhea Permatasari; Destrinelli Destrinelli; Issaura Sherly Pamela (Journal on Education, 2023)
Students' creative thinking skills are the ability to process some information that can produce new ideas in the learning process. This research is a classroom action research that consists of two cycles, each of which is carried out in two meetings. Each cycle consists of 4 stages, namely (1) action planning, (2) action implementation, (3) observation and (4) reflection. Data collection in this study included conducting interviews, observing through observation sheets on students' creative thinking skills, teacher activity sheets in carrying out learning using project-based learning models and documentation. This research was conducted in class IV B of SDN 64/I Muara Bulian. The results of this study indicate that the application of the project based learning model in social studies learning for class IV is able to improve students' creative thinking skills. This increase can be seen in the data analysis at each cycle meeting. Cycle I, the level of creative thinking ability was 44.44%. Then it increased in cycle II by 43%, so that the proportion value was 87.50%. Based on the results of the research that has been carried out, it can be concluded that the application of the project based learning model is able to improve creative thinking skills as seen from the increase which has reached more than 75% or as many as 21 students are able to meet the indicators of research success.